Is There a Potential of Misuse for Venlafaxine and Bupropion? - Schifano, Fabrizio; Chiappini, Stefania (Frontiers in Pharmacology, 2018)
ABSTRACT Objective: Traditionally, studies on the nonmedical use of pharmaceutical products have focused on controlled substances; e.g. opiates/opioids; and benzodiazepines. Although both bupropion and venlafaxine have been reported as being misused, only anecdotal reports have been made available so far. Hence, the European Monitoring Agency (EMA) Adverse Drug Reactions (ADRs), misuse/abuse/dependence and withdrawal, venlafaxine- and bupropion-related, database was here analyzed. Methods: All EMA spontaneous reports relating to venlafaxine (2005-2016) and bupropion (2003-2016) notifications were here analyzed, to provide a descriptive analysis by source, gender, age, and type of report. The UK-based, 2000-2016, Yellow Card Scheme pharmacovigilance database, bupropion and venlafaxine withdrawal reports were compared as well with those pertaining to fluoxetine and paroxetine. Results: Out of 20,720 (bupropion) and 47,516 (venlafaxine) total number of ADRs, some 2,232 (10.8%), and 4,071 (8.5%) misuse/abuse/dependence ADRs were respectively associated with bupropion and venlafaxine. Conversely, bupropion withdrawal-related ADRs were here reported in 299/20,720 (1.44%) cases and in 914/47,516 (1.92%) cases for venlafaxine. Overall, all bupropion and venlafaxine misuse-/abuse-/dependence- and withdrawal-ADRs were related to a respective number of 264 and 447 patients. According to the Proportional Reporting Ratio (PRR) computation, in comparison with venlafaxine bupropion resulted to be more frequently misused/abused (PRR: 1.50), but less frequently associated with both dependence (PRR: 0.92) and withdrawal (PRR: 0.77) issues. Yellow Card Scheme data suggested that paroxetine and venlafaxine, in comparison with fluoxetine and bupropion, were associated with higher number of withdrawal-related reports. Conclusions: The dopaminergic, stimulant-like, bupropion activities may be associated with its possible recreational value. Present data may confirm that the occurrence of a withdrawal syndrome may be a significant issue for venlafaxine-treated patients.